An overview of low back pain and occupational exposures to whole-body vibration and mechanical shocks - Bovenzi, Massimo; Schust, Marianne; Mauro, Marcella (La Medicina del Lavoro, 2017)
This paper offers an overview of the relation of low back pain (LBP) to occupational exposures to whole-body vibration (WBV) and mechanical shocks. LBP is a condition of multifactorial origin and is a very common health problem in the general population. Among occupational risk factors, epidemiological studies of driving occupations have provided evidence for strong associations between LBP and occupational exposures to WBV and mechanical shocks. Since it is hard to separate the contribution of WBV exposure to disorders in the lower back from that of other individual, ergonomic or psychosocial risk factors, a quantitative exposure-response relationship for WBV cannot be outlined precisely. Experimental research has provided biodynamic support to the findings of epidemiological studies, showing that in controlled laboratory conditions exposure to WBV can cause mechanical overload to the human spine. The EU Directive on mechanical vibration has established daily exposure action and limit values to protect the workers against the risk from WBV. There is some evidence that the EU exposure limit values are excessive, so much so that an elevated risk of LBP has been found for WBV exposures beneath the EU limit values. In the Italian arm of the EU VIBRISKS prospective cohort study of professional drivers, measures of internal lumbar load (compressive and shear peak forces), calculated by means of anatomy-based finite-element models, were found better predictors of the occurrence over time of low back disorders than the metrics of external exposure suggested by the EU Directive on mechanical vibration. Further biodynamic and epidemiological studies are needed to validate the findings of the VIBRISKS study.